Economic Empowerment of Tourism Conscious Housewives Through Social Media Marketing and Product Packaging Design : Pemberdayaan Ekonomi Ibu Rumah Sadar Wisata Melalui Pemasaran Sosial Media dan Desain Pengemasan Produk - Khatimah, Husnil; Abel Tasman; Wiwik Indrayeni (Universitas Lancang Kuning, 2023)
The Community Partnership Program aims to provide education and assist partners in solving priority problems by using strategic aspects of marketing, finance and product design in the form of a simple and easy to run business model that includes aspects of main partners, main activities and value propositions. The partner for this PKM activity is the Tourism Awareness Women's Group in the East Timbulan Painan tourist area in IV Jurai District, South Coast. In PKM activities, partners will collaborate and be involved in the training provided in the form of creating a business website, assisting in creating promotional content on social media, discussing variations and packaging of business products, as well as how to collaborate with outside parties, managing business finances so that partners are able to increase income. in terms of production and marketing. This PKM is expected to be able to contribute to the community, especially to POKDARWIS women independently and sustainably in accordance with government programs to improve the community's economy in local tourist destinations. The specific targets for this activity are: 1) Increase in partner turnover; 2) Increasing competitiveness (HR, raw materials, production processes, products, marketing; 3) Increasing the quality of partner/SME management (level of IT use, completeness of standard management procedures; 4) Product packaging design, social media content; 5) Increased understanding and skills of partners. The approach methods offered to solve partner problems are 1) Providing training on creating business websites that are used to market pastries and traditional food business products; 2) Increasing knowledge insight through assistance in creating product content that will be promoted through social media; 3) Provide packaging design training for pastries and traditional food businesses with certain characteristics; 4) increase the broadest knowledge of partners regarding business cooperation so that business capital does not rely on personal sources.